Pancasila and an Attempt to Revitalize Religious Tolerance in Yogyakarta - Alif Lukmanul Hakim (SOSIOHUMANIORA: Jurnal Ilmiah Ilmu Sosial dan Humaniora, 2021)
The background of this paper is because of the socio-cultural and religious problems around us, which are increasingly complex and multidimensional, the values and culture of tolerance among religious people as well as between religious communities are increasingly being eroded and are no longer used as guidelines in behaving in everyday life. The Indonesian nation is a plural and pluralistic nation. Therefore plurality cannot be eliminated, but it needs to be adequately managed not negatively to impact tolerance and the application of Pancasila values. Tolerance, namely, allowing other people to think differently, to do things that do not agree with us. Without us being bothered or intimidated or in a social, cultural and religious context, attitudes and actions prohibit discrimination against different groups or are unacceptable by the community. This study uses a qualitative method with the formal object is Pancasila, and the material object is religious intolerance in Yogyakarta. This study finds values that must be realized to increase religious tolerance in Indonesia, especially in Yogyakarta.